2008
DOI: 10.1080/14675980802531598
|View full text |Cite
|
Sign up to set email alerts
|

The children of guest workers: comparative analysis of scholastic achievement of pupils of Turkish origin throughout Europe

Abstract: This paper examines the integration of Turkish labour migrant children in four countries across Europe in terms of their educational performance. By looking at the PISA 2003 (Programme for International Student Assessment) data pertaining to mathematics achievement of 15-year-olds, it explores the effects of ethnicity, gender and family background, on the one hand, and institutional factors (such as kindergarten attendance, grading and tracking), on the other, to offer a better understanding of the large immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…International tests showed immigrant students perform below average in key school subjects, such as mathematics, reading and science, the subjects most important for their educational career (OECD 2004(OECD , 2006Pásztor 2008). The results indicated that Turkish pupils often have to repeat one or two school years during compulsory schooling and almost a quarter (23%) do not understand German texts (not even at the basic level) at the age of 15 (Pásztor 2008).…”
Section: Immigrant Children In the Austrian Educational Systemmentioning
confidence: 92%
“…International tests showed immigrant students perform below average in key school subjects, such as mathematics, reading and science, the subjects most important for their educational career (OECD 2004(OECD , 2006Pásztor 2008). The results indicated that Turkish pupils often have to repeat one or two school years during compulsory schooling and almost a quarter (23%) do not understand German texts (not even at the basic level) at the age of 15 (Pásztor 2008).…”
Section: Immigrant Children In the Austrian Educational Systemmentioning
confidence: 92%
“…The findings of Han and colleagues' (2012) study demonstrated that preschool education experience do positively impact immigrant children's academic skills, nevertheless immigrant children continue to perform lower on most academic tasks than their native peers. Studies reporting the secondary analysis of the Program for International Student Assessment data demonstrated that despite the legal and pedagogical regulations and reforms the academic achievement gap between the native and immigrant children in Europe persists into the upper grades (Jensen & Rasmussen, 2011;Pásztor, 2008;Schnepf, 2008;Taguma, Kim, Brink & Telteman, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The educational situation of second-generation Turks in Austria well reflects that of their parents, three quarter of which had no more than compulsory schooling (77%) upon arrival to Austria (Pásztor, 2008). Their children who use the Turkish language at home are likely to be found in the least selective secondary school tracks, while many are channelled to special schools.…”
Section: Mapping the Educational Landscapementioning
confidence: 97%
“…The first four International Studies in Sociology of Education 291 years of schooling do not necessarily allow Turkish pupils to catch up with their peers as they first have to come to terms with learning the German language (Pásztor, 2008). Thus, the selection point at the age of 10 disadvantages immigrant children who are often Early selection is generally associated with greater social\-class inequalities while educational systems delaying the time of selection tend to be more egalitarian (Breen & Jonsson, 2005, Kerkhoff, 1995.…”
Section: Mapping the Educational Landscapementioning
confidence: 97%